Texture element on design / Aiman Hakim Mohd Yusof - Mohd Yusof, Aiman Hakim (Faculty of Art and Design, 2020)
The texture is an element of design that defines the surfaces of shapes and forms. The texture is defined as the tactile quality of the surface of an object -how it feels touched. But it is so much more than that. The texture that we feel with your fingers is called tactile, while the texture that the artist recreates on a flat surface is called visual texture. Tactile texture is three-dimensional because it has height. width and depth. Visual texture is two-dimensional because it lacks real depth. Objects all around us provide examples of tactile texture.